2017
DOI: 10.1111/rda.12956
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance of postpartum ewes treated with insulin or progesterone hormones in association with ram effect

Abstract: The reproductive performance of postpartum Santa Inês (SI) and Morada Nova (MN) ewes treated with insulin or progesterone hormones in association with ram effect was evaluated. Ewes from SI (n = 69) and MN (n = 69) breeds were randomly allocated to three groups of each breed (T1-ram effect only; T2-ram effect + insulin; T3-ram effect + progesterone). Progesterone concentrations (ηg/ml; mean ± SD) before and after introduction of rams (n = 6) were 0.51 ± 0.22 and 3.78 ± 0.68 (T1), 0.65 ± 0.21 and 3.77 ± 0.78 (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…From a productive standpoint, the Santa Inês breed, which originated from crosses of exotic and Brazilian native breeds, is character-96 J. C. Ferreira-Silva et al: Progesterone (P4), luteinizing hormone (LH) levels in postpartum Santa Inês ewes ized by a large size, where ewes weigh from 40 to 60 kg and rams from 80 to 100 kg, although they may reach 120 kg (Figueiredo et al, 1983). From a reproductive standpoint, ewes are continuously polyestrous, with prolificacy varying from 1.3 to 1.4, and have maternal ability , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…From a productive standpoint, the Santa Inês breed, which originated from crosses of exotic and Brazilian native breeds, is character-96 J. C. Ferreira-Silva et al: Progesterone (P4), luteinizing hormone (LH) levels in postpartum Santa Inês ewes ized by a large size, where ewes weigh from 40 to 60 kg and rams from 80 to 100 kg, although they may reach 120 kg (Figueiredo et al, 1983). From a reproductive standpoint, ewes are continuously polyestrous, with prolificacy varying from 1.3 to 1.4, and have maternal ability , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…In cattle, this interval ranges from 14 to 69 days, depending on whether the female is being milked or suckled (McDougall et al., 1995; Rajamahendran & Taylor, 1990; Rawlings et al., 1980; Savio et al., 1990; Webb et al., 1980). Previous studies on ungulates have shown that factors such as suckling (Hinshelwood et al., 1982; Webb et al., 1980), photoperiod (Llewelyn et al., 1992; Santos et al., 2009; Savio et al., 1990), nutrition (Hinshelwood et al., 1982; Santos et al., 2009; Savio et al., 1990), exposure to a male (Ferreira‐Silva et al., 2017; Gifford et al., 1989) and parity (Hinshelwood et al., 1982; Santos et al., 2009; Tanaka et al., 2008) may influence the interval from post‐partum up to the return of oestrous cyclicity. The females monitored in this study were suckled, exposed to males, and calving occurred during the southern hemisphere winter.…”
Section: Discussionmentioning
confidence: 99%
“…Restricting the time of ewe-lamb interaction or suckling restriction, though time consuming, has proven to be an effective strategy to reduce the length of postpartum anestrus (Morales-Teran, Pro-Martinez, Figueroa-Sandoval, Sanchez-del-real, & Gallegos-Sanchez, 2004;Oliveira et al, 2013). The male effect is also effective in shortening the duration of anestrus in ewes (Ferreira-Silva et al, 2017), but there is a suggestion that a minimum time of separation between lambs and ewes is required to improve reproductive response (Pevsner, Rodrguez-Iglesias, & Ciccioli, 2010). However, others have not mentioned such a requirement (Fraire-Cordero et al, 2018).…”
Section: Introductionmentioning
confidence: 99%